The simultaneous generation of soliton bunches and Q-switched-like pulses in a partially mode-locked fiber laser with a graphene saturable absorber. (26th March 2018) - Wang, Zhenhong; Wang, Zhi; Liu, Yan-ge; He, Ruijing; Wang, Guangdou; Yang, Guang; Han, Simeng
Abstract: We experimentally report the coexistence of soliton bunches and Q -switched-like pulses in a partially mode-locked fiber laser with a microfiber-based graphene saturable absorber. The soliton bunches, like isolated spikes with extreme amplitude and ultrashort duration, randomly generate in the background of the Q -switched-like pulses. The soliton bunches have some pulse envelopes in which pulses operate at a fundamental repetition rate in the temporal domain. Further investigation shows that the composite pulses are highly correlated with the noise-like pulses. Our work can make a further contribution to enrich the understanding of the nonlinear dynamics in fiber lasers.